Neuer Atheismus: New Atheism in Germany - Zenk, Thomas (Approaching Religion, 2012)
Matthias Knutzen (born 1646 – died after 1674) was the first author we know of who self-identified as an atheist (Schröder 2010: 8). Before this, the term had solely been used pejoratively to label others. While Knutzen is almost completely forgotten now, authors such as Ludwig Feuerbach, Karl Marx, Friedrich Nietzsche, or Sigmund Freud are better remembered and might even be considered classic writers in the history of the atheist criticism of religion. Whatever may be said about the influence of any one of these authors, there is no doubt that Germany looks back on a notable history in this field. About a decade ago, Germany’s capital Berlin was even dubbed ‘the world capital of atheism’ by the American sociologist Peter L. Berger (2001: 195).Given this situation, I am bewildered by the expression ‘New Atheism’. Yet, undoubtedly, the term has become a catchphrase that is commonly used in the public discourse of several countries. The most prominent authors to be labelled ‘New Atheists’ are Richard Dawkins (The God Delusion, 2006), Daniel Dennett (Breaking the Spell: Religion as a Natural Phenomenon, 2006), Sam Harris (The End of Faith: Religion, Terror, and the Future of Reason, 2004, and Letter to a Christian Nation, 2006), and Christopher Hitchens (God Is Not Great: How Religion Poisons Everything, 2007). These authors and their books – all of them international bestsellers – have been intensely discussed around the world, including in Germany. In this paper, I intend to illuminate some of the characteristics and remarkable traits of the German discourse on the ‘New Atheism’. Here we can distinguish between two phases. The German media initially characterised ‘New Atheism’ as a rather peculiarly American phenomenon. However, it soon came to be understood to be a part of German culture as well.